NERACA AIR DAS NANGALILI (WATER BALANCE ANALYSIS IN NANGALILI WATERSHED) - Danang Bimo Irianto; Kiki Frida Sulistyani (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2018)
Nangalili Is a watershed that has a very wide area in WS Flores, it is 843.73 km2 and is located in two districts ,Manggarai and West Manggarai. Das Nangalili has a potential large water availability that is 595,449 Million m3 / year. The Nangalili watershed also has diverse water needs ranging from irrigation, livestock, household, urban, industrial and river maintenance. In Nangalili watershed there is also Irrigation Area with functional area of 3954Ha. Nangalili watershed is divided into 17 sub watersheds and its water balance calculations are held at 13 locations. From the anual water balance analisys, the result are deficit in 4 location and surplus in 9 location surplus with deficit in period 10 days in certain months with percentage of deficit between 16,7% until. 47.2%. • The deficit location on yearly basis are Wae Lombur Dam, Wae Sele's Bend, Wae Cewo's Bend and Bendung Wae Sesap.